The impact of minimum wages on well-being: Evidence from a quasi-experiment in Germany - Filiz Gülal; Adam Ayaita (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
To analyze well-being effects of minimum wages, the introduction of a minimum wage in Germany in 2015 is used as a quasi-experiment. Based on the representative SOEP data, a difference-in-differences design compares the development of life, job, and pay satisfaction between those who are affected by the reform according to their pre-intervention wages and those who already have marginally higher wages so that they are not directly affected. The results show that the minimum wage has significantly positive effects on all considered dimensions of well-being, on average, with an increase in life satisfaction by 0.10 standard deviations (0.15 points on a ten-point Likert scale). Positive effects last at least until one year after the reform. Life satisfaction tends to increase particularly in the region that is overall economically less developed (East Germany). The results hold if those who are not employed anymore after the reform are included in the analysis.
Keywords: I31; J28; J30; J31; J38; J60; 330; minimum wage; natural experiments; well-being; satisfaction